Towards building caring communities: imagining alterity with mushrooms - Kok, Charmaine Xi Mun (Nanyang Technological University, 2022)
Oft-touted as a “successful model of state capitalism” (Völgyi, 2019, pp. 275), Singapore continuously speeds towards a future in which its government holds significant power over all dimensions of its citizen’s lives. Here, the simultaneous forces of capitalism and paternalism under the state results in a society predicated on hierarchy and subjugation, where stringent control is exercised over the private lives of its people, while civil liberties and participation in the public sphere are limited and regulated. In this dog-eat-dog environment, a false and competitive belief in scarcity takes hold, alienating people as relationships between individuals skew towards replicating systems of power, allowing indifference, suspicion and hostility to proliferate. Within such circumstances, individuals might consequently defect instead to apathy, and are incentivised to care in stunted and exclusive ways — assuming responsibility only for themselves, or their most immediate contacts.